Microbiological Quality of Heat-Treated Milk During Storage - Ahmed Hassan, Nagla Bourae; Mohamed Abdalla, Mohamed Osman; Mohamed Nour, Abdel Azim Ahmed (Pakistan Journal of Nutrition, 2009)
This study was carried out to evaluate the microbial load of heat treated milk during storage. Collected raw milk samples were subjected to heat treatment at 98oC for 1.87 min (High Pasteurization, HP) and 85oC for 40 min (Low Pasteurization, LP) in addition to Ultra High Temperature Treated (UHT) milk samples which were purchased from local market. Milk samples were subjected to microbial examination, titratable acidity and pH at 1, 10, 20 and 30 day intervals. Results indicated that total bacteria and lactic acid bacteria count significantly increased with time during storage period, together with increase in titratable acidity of all samples tested, while pH gradually decreased towards the end. The following genera were isolated from milk samples: Bacillus, Micrococcus, Saphylococcus, Enterobacter, Pseudomonas, Streptococcus, Pediococcus and Lactobacillus.